Identificação do sexo e variabilidade genética em uma população de Astronotus ocellatus (Agassiz, 1831) por marcadores ISSR - Paiva, Isadora Marques (2015)
Studies conducted in order to investigate alternative methods for sexing fish species, such as Astronotus ocellatus, using reduced sexual dimorphism, are extremely important to facilitate reproduction management techniques. The objective of this study was to determine the feasibility of manual sexing, widely used by fish farmers and hobbyists, and the identification of specific molecular markers for a particular sex using ISSR markers. The latter technique also generates genetic diversity and similarity data, and is important for conservation studies. Manual sexing was performed by macroscopic analysis of the urogenital papilla. Fin and gonad samples of 30 A. ocellatus (±83,32g e ±15, 96 cm) were collected for DNA extraction and histology, respectively. For DNA extraction, we adopted the NaCl protocol (SAMBROOK, 1989). Quality samples were used for amplification, using universal ISSR primers with subsequent separation of the generated fragments by electrophoresis, and assessment of similarity and genetic diversity levels. The manual sexing did not appear as a viable technique to distinguish the sexes for this species, given the occurrence of 37% of errors during selection. Likewise, the band profiles generated by the amplification with ISSR primers could not distinguish a specific pattern for one sex. The percentage of polymorphism (64,4%) obtained, as well as He and I indexes (0.225 ± 0.030 and 0.375 ± 0.044, respectively) suggest moderate diversity, indicating that marked captive populations do not always decrease in genetic diversity.